Rapid photocatalytic reduction of graphene oxide indirectly activated by the domino effect of ethanol oxidation on a titanium dioxide film - Duy, Le Thai; Kalanur, Shankara S.; Cho, In Sun; Seo, Hyungtak (Materials Chemistry and Physics, 2018)
Deoxygenation of graphene oxide is a low-cost and effective way to yield graphene (i.e., reduced graphene oxide - RGO) for many applications. However, choices of reduction approach and reduction time need consideration due to damaging pre-existing materials on electronic devices. Here, we found a facile and eco-friendly route that was based on the photo-oxidation of ethanol (diluted in water) on a catalytic TiO2 film to rapidly induce the formation of RGO within 15 min under UV (20 mW/cm2) or sun lights (1 sun = 100 mW/cm2). Our reduction route was indirectly activated by chain reactions of ethanol and TiO2 (so-called domino effect) because the GO deoxygenation occurred even when the samples were placed around and not in contact with TiO2 film. To obtain the highest reduction, the samples should stay on the catalytic film to receive lights for activation and acceleration of reactions. Furthermore, effects of exposure time (1–20 min), ethanol concentration (14.3–100%), and light intensity on RGO quality explored with the use of chemiresistive devices. The results of demonstrative sensing measurements towards NO2 and NH3 indicate that our method is promising for electrical applications using solution processable RGO.
Keywords: Domino effects; Ethanol oxidation; Rapid reduction; Reduced graphene oxides; TiO2 film; Domino effect; Ethanol oxidation; Rapid reduction; Reduced graphene oxide; TiO2 film